Environmental stewardship: A systematic scoping review. - Lynette J McLeod; Jane C Kitson; Zack Dorner; Natasha A Tassell-Matamua; Philip Stahlmann-Brown; Taciano L Milfont; Donald W Hine (PLoS ONE)
Environmental stewardship is a term describing both the philosophy and the actions required to protect, restore, and sustainably use natural resources for the future benefit of the environment and society. In this paper, we review the environmental science literature to map the types of practical actions that are identified as 'environmental stewardship' using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for scoping reviews. We specifically mapped: 1) the type of actions and outcomes targeting the natural environment that have been categorized as environmental stewardship, 2) the main actors, and the underlying factors influencing their environmental stewardship actions, and 3) the methods used to mobilize environmental stewardship actions once these factors are known. From the 77 selected articles, we found the term environmental stewardship encompassed a multitude of different actions, undertaken by a range of actors and addressing an array of issues that impact biodiversity on the land and in the water. These stewardship actions were conducted on both privately-owned and publicly managed lands and waterways, and across rural and urban landscapes. Despite many studies identifying characteristics and underlying behavioral factors that predicted actors' participation in stewardship actions, there were few studies formally evaluating interventions to increase stewardship. Our review highlighted the term environmental stewardship is not embraced by all and is viewed by some as being inconsistent with aspects of indigenous worldviews. A better understanding of the concept of environmental stewardship and continued practical research into its practice is fundamental to empowering people to demand and enact environmental stewardship as well as for evaluating the success of their actions.